2016
DOI: 10.1088/1367-2630/18/8/083036
|View full text |Cite
|
Sign up to set email alerts
|

Full reconstruction of a 14-qubit state within four hours

Abstract: Full quantum state tomography (FQST) plays a unique role in the estimation of the state of a quantum system without a priori knowledge or assumptions. Unfortunately, since FQST requires informationally (over)complete measurements, both the number of measurement bases and the computational complexity of data processing suffer an exponential growth with the size of the quantum system. A 14-qubit entangled state has already been experimentally prepared in an ion trap, and the data processing capability for FQST o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
46
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 89 publications
(46 citation statements)
references
References 42 publications
0
46
0
Order By: Relevance
“…New systems and methods for preparing * e-mail:anton.frisk.kockum@gmail.com and measuring such entangled states has therefore been sought intensively for a long time , and remains a very active field of research. In recent years, entanglement of ten or more qubits has been demonstrated in various experimental setups [45][46][47][48][49].…”
Section: Introductionmentioning
confidence: 99%
“…New systems and methods for preparing * e-mail:anton.frisk.kockum@gmail.com and measuring such entangled states has therefore been sought intensively for a long time , and remains a very active field of research. In recent years, entanglement of ten or more qubits has been demonstrated in various experimental setups [45][46][47][48][49].…”
Section: Introductionmentioning
confidence: 99%
“…If we look at the example of N qubits, which will be our thread in this paper, one has to make at least 2 N + 1 measurements in different bases before to determine the state of a priori unknown system [3][4][5][6]. With such an exponential scaling, it is clear that only few-qubit states can be reconstructed in a reasonable time [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…To give another example, in Ref. [14] it was shown that, in reconstructing a 14-qubit state, using both smart choice of the state representation and parallel graphic processing unit programming can speed up the post-processing by a factor of 10 4 . Besides of these technical improvements, there also exist various theoretical approaches that are devoted to enhance the capability of quantum state tomography [15][16][17].…”
Section: Introductionmentioning
confidence: 99%